Hubungan antara kebolehsuaian kerjaya dan komitmen organisasi dalam sector awam terpilih - Norafizah, Baharin (Universiti Malaysia Sarawak, 2019)
The purpose of this study is to identify the relationship between career adaptability and organizational commitment by using quantitative methods. The independent variables in this study are the dimensions of career adaptability comprising concern, control, curiosity and confidence. While organizational commitment plays an important role as a dependent variable. This study is a survey which involves the use of questionnaires in data collection. Respondents who had taken were 248 people to fill the questionnaires that had been distributed. The questionnaire used was adaptation from previous researcher. The data collected were analyzed using the Statistical Package for Social Science Version 20.0 (SPSS Version 20.0). The relationship between career adaptability and organizational commitment was analyzed using the Pearson Correlation Analysis. The results of this study show a significant relationship between career adaptability and organizational commitment.